Analysis of The Properties and Quick of Wave Creation on A Simple Ripple Tank Using Frequency Sensors - Anisa Furtakhul Janah; M. Iqbal Sugita; Hartono Hartono; Supriyadi Supriyadi (Journal of Natural Sciences and Mathematics Research, 2019)
Practicum is one of the effective methods for students in learning Natural Sciences (IPA), especially Physics subjects. The purpose of the practicum is to make it easier for students to understand concepts and help explain physics concepts that cannot be observed directly by the eye. The 2013 curriculum demands physics learning to integrate various concepts, so that students have a thorough understanding of a phenomenon. This study aims to determine the effect of spring strain and tube length on the speed of propagation and wavelength. Ripple tank experiments that currently exist, only calculate variations in fluid height, gap size, vibrator frequency, and so on. The method used in this research is experimental, for the components used consist of a set of simple ripple tank tools and frequency sensors. The analytical technique used in this research is descriptive quantitative. The highest and lowest frequencies produced from the small tube were 20 Hz (l=70 cm; = 0.04 cm) and 1 Hz (l=5 cm; = 4.30 cm). The highest and lowest frequencies obtained from the large tube were 52 Hz (l=70 cm; = 0.05 cm) and 3 Hz (l=5 cm; = 4.95 cm). The highest and lowest wave propagation velocities produced by the small tube are 4.3 cm/s (l=5 cm) and 0.89 cm/s (l=70 cm). The highest and lowest wave propagation velocities produced by the large tube are 9.87 cm/s (l=5 cm) and 2.69 (l=70 cm). Based on the results of the study, it was shown that the greater the spring strain, the higher the frequency, the wavelength and the speed of wave propagation.©2019 JNSMR UIN Walisongo. All rights reserved.